Pilot study on the development of a low cost land observation and geo-information retrieval system for emergency monitoring of agricultural crop and disaster-induced damages - Haque, Md. Mojammel; Talukder, Bijoy; Huda, Aynul; Chayan, Sanando Jagati (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.